A Randomized Placebo-Controlled Dose-Response Trial of Muvz™ for Knee and Low-Back Support in Physically Active Adults - Kalman D; Srivastava S; Desale A; Chatte Snr MD; Nalavade RJ; Shah Snr KM; Karvir S; Bhasale S (Drug Design, Development and Therapy)
Douglas Kalman,1 Shalini Srivastava,2 Ajinkya Desale,3 Manish Devidas Chatte Snr,4 Rohit J Nalavade,5 Kshitij Manoj Shah Snr,6 Sagar Karvir,7 Surendra Bhasale8 1Department of Nutrition, Dr. Kiran c Patel College of Osteopathic Medicine, Nova Southeastern University, Ft, Lauderdale, Florida, USA; 2Clinical Development Department, Vedic Lifesciences Pvt. Ltd., Mumbai, Maharashtra, India; 3Life Care Hospital, Nashik, Maharashtra, India; 4Sankalp Hospital, Nashik, Maharashtra, India; 5Sparsh Superspeciality Hospital, Panvel, Maharashtra, India; 6Proactive Orthopedic Clinic, Mumbai, Maharashtra, India; 7Ayush Nursing Home, Mumbai, Maharashtra, India; 8Diamond Orthopedic & Multispecialty Hospital, Mumbai, Maharashtra, IndiaCorrespondence: Shalini Srivastava, Vedic Lifesciences Pvt. Ltd, Morya House, 118-B, off Link Road, Andheri West, Mumbai, Maharashtra, 400053, India, Tel +91 9619477885, Email shalini.s@vediclifesciences.comPurpose: The current study aimed to investigate the dose-response efficacy and safety of MuvzTM (E-PR-01, a blend of V. negundo and Z. officinale) in 400 mg (High-dose [HD]) and 200 mg (Low-dose [LD]) of daily dose in physically active adults in 90 days.Patients and Methods: The study included 157 adults aged 40– 60 having knee/low back joint discomfort. The primary outcome was an enhancement in the overall musculoskeletal health in 90 days. Secondary outcomes included assessing the joint discomfort following physical activity, range of motion, quality of life, and the consumption of rescue medication.Results: E-PR-01 notably enhanced musculoskeletal health in a dose-dependent manner compared to placebo within 30 days (p< 0.0001), with effects persisting through day 90 and demonstrated clinically significant difference by 13 and 10 units in the HD and LD groups, respectively. Joint discomfort reduced significantly in both the E-PR-01 groups by day 90 (p< 0.0001). Furthermore, both doses of E-PR-01 improved the range of motion of the assessed joint (p< 0.05) and enriched participants’ overall quality of life (p< 0.05) at the end of the study.Conclusion: The study finds E-PR-01 effective for improving overall joint health, with the higher dose showing greater efficacy. These findings align with the earlier studies of E-PR-01 for knee and low back discomfort.Keywords: low back pain, knee joint, Zingiber officinale, range of motion, placebo-controlled, Vedic Lifesciences, dietary supplement